Rhizobia as a Source of Plant Growth-Promoting Molecules: Potential Applications and Possible Operational Mechanisms - Jaiswal, Sanjay K.; Mohammed, Mustapha; Ibny, Fadimata Y. I.; Dakora, Felix D. (Frontiers in Sustainable Food Systems, 2021)
The symbiotic interaction between rhizobia and legumes that leads to nodule formation is a complex chemical conversation involving plant release of nod-gene inducing signal molecules and bacterial secretion of lipo-chito-oligossacharide nodulation factors. During this process, the rhizobia and their legume hosts can synthesize and release various phytohormones, such as IAA, lumichrome, riboflavin, lipo-chito-oligossacharide Nod factors, rhizobitoxine, gibberellins, jasmonates, brassinosteroids, ethylene, cytokinins and the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase that can directly or indirectly stimulate plant growth. Whereas these attributes may promote plant adaptation to various edapho-climatic stresses including the limitations in nutrient elements required for plant growth promotion, tapping their full potential requires understanding of the mechanisms involved in their action. In this regard, several N2-fixing rhizobia have been cited for plant growth promotion by solubilizing soil-bound P in the rhizosphere via the synthesis of gluconic acid under the control of pyrroloquinoline quinone (PQQ) genes, just as others are known for the synthesis and release of siderophores for enhanced Fe nutrition in plants, the chelation of heavy metals in the reclamation of contaminated soils, and as biocontrol agents against diseases. Some of these metabolites can enhance plant growth via the suppression of the deleterious effects of other antagonistic molecules, as exemplified by the reduction in the deleterious effect of ethylene by ACC deaminase synthesized by rhizobia. Although symbiotic rhizobia are capable of triggering biological outcomes with direct and indirect effects on plant mineral nutrition, insect pest and disease resistance, a greater understanding of the mechanisms involved remains a challenge in tapping the maximum benefits of the molecules involved. Rather than the effects of individual rhizobial or plant metabolites however, a deeper understanding of their synergistic interactions may be useful in alleviating the effects of multiple plant stress factors for increased growth and productivity.